Research on the Fit between Douyin Video Creativity and User Psychological Needs - Xiao, Wenqi (Transactions on Social Science, Education and Humanities Research, 2024)
Douyin, a short video application, has swept the globe, becoming an essential tool for millions of users. Behind its success lies a profound charm: the deep fit between video creativity and user psychological needs. This alignment not only brings users an ultimate sense of satisfaction and pleasure but also builds a solid barrier of user stickiness for the Douyin platform. The video creativity on Douyin is diverse, covering humor, dance, food, travel, knowledge sharing, and other fields. The creative content is not merely entertainment but accurately captures and meets users’ psychological needs. In the fast-paced life, people are eager to find a way to relax and relieve stress, and Douyin is such a perfect choice. Therefore, studying the fit between Douyin video creativity and user psychological needs is crucial for enhancing the user experience and attractiveness of the Douyin platform. By deeply understanding users’ psychological needs, Douyin can continuously optimize video creativity to provide users with higher quality, need-matching content. This is undoubtedly key to maintaining competitiveness and continuously attracting users.